INFLUENCE OF DISTRIBUTION CHANNELS AND INFORMATION SYSTEMS MARKETING TO SALES EFFECTIVENESS PT. THE GREAT STAR OF MEDAN'S SUCCESS - Winnie; Syawaluddin; Aidil Putra; Thomas Sumarsan Goh (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
This research was conducted on consumers who work at PT. Bintang Agung Sukses Medan. The purpose of this study is to determine and analyze the effect of distribution channels and marketing information systems on sales effectiveness. The population and sample in this study amounted to 42 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously distribution channels and marketing information systems have a positive and significant effect on the sales effectiveness of PT. Bintang Agung Sukses Medan. Partially, the distribution channel has an effect on the sales effectiveness of PT. Bintang Agung Sukses Medan. Partially, the marketing information system has a positive and significant effect on the sales effectiveness of PT. Bintang Agung Sukses Medan. The magnitude of the coefficient of determination can be seen from the Adjusted R Square value is: 0.341 means that Distribution Channels and Marketing Information Systems are able to explain Sales Effectiveness by 34.1% while the remaining 65.9% is influenced by variables not examined such as: product discounts, market segmentation, product prices, and so on.